Pathogen-dependent role of turbot (Scophthalmus maximus) interferon-gamma - Pereiro, Patricia; Forn-Cuni, Gabriel; Figueras Huerta, Antonio; Novoa, Beatriz (Fish & Shellfish Immunology, 2016)
11 páginas, 7 figuras Interferon-gamma has been typically described as a pro-inflammatory cytokine playing an important role in the resolution of both viral and bacterial diseases. Nevertheless, some anti-inflammatory functions are also attributed to this molecule. In this work we have characterized for the first time the turbot (Scophthalmus maximus) interferon-gamma gene (ifng) and its expression pattern under basal conditions, after type I IFNs administration, and viral and bacterial infection. The intramuscular injection of an expression plasmid encoding turbot Ifng (pMCV1.4-ifng) was not able to affect the transcription of numerous immune genes directly related to the activity of IFN-gamma, with the exception of macrophage-colony stimulating factor (csf1). It was also unable to reduce the mortality caused by a Viral Hemorrhagic Septicemia Virus (VHSV) or Aeromonas salmonicida challenge. Interestingly, at 24 h post-infection, turbot previously inoculated with pMCV1.4-ifng and infected with VHSV showed an increase in the expression of pro-inflammatory cytokines and type I IFNs compared to those fish not receiving expression plasmid, indicating a synergic effect of Ifng and VHSV. On the other hand, some macrophage markers, such as the macrophage receptor with collagenous structure (marco), were down-regulated by Ifng during the viral infection. Ifng had the opposite effect in those turbot infected with the bacteria, showing a reduction in the transcription of pro-inflammatory and type I IFNs genes, and an increase in the expression of genes related to the activity of macrophages This work has been funded by the projects CSD2007-00002 “Aquagenomics”, 201230E057 (CSIC) and AGL2014-51773-C3 from the Spanish Ministerio de Economía y Competitividad. P. Pereiro received a predoctoral grant from the gs3:Ministerio de Educación [F.P.U. fellowship AP2010-2408] Peer reviewed